Algae and bacteria consortia for wastewater decontamination and transformation into biodiesel, bioethanol, biohydrogen, biofertilizers and animal feed: a review - Uttpal Anand; Satarupa Dey; Dipannita Parial; Stefania Federici; Serena Ducoli; Nanthi S. Bolan; Abhijit Dey; Elza Bontempi (Environmental Chemistry Letters, 2023)
Traditional wastewater treatment has been aimed solely at sanitation by removing contaminants, yet actual issues of climate change and depletion of natural resources are calling for methods that both remove contaminants and convert waste into chemicals and fuels. In particular, biological treatments with synergic coupling of microalgae and bacteria appear promising to remove organic, inorganic, and pathogen contaminants and to generate biofuels. Here, we review the use of algae and bacteria in the treatment and valorization of wastewater with focus on cell-to-cell adhesion, wastewater properties, and techniques for algae harvesting and production of biodiesel, bioethanol, biohydrogen, exopolysaccarides, biofertilizers, and animal feeds.